2012
DOI: 10.1002/poc.3026
|View full text |Cite
|
Sign up to set email alerts
|

Determining the excited‐state substituent constants of meta‐substituent from 3,4'‐disubstituted stilbenes

Abstract: In this paper, 61 samples of 3,4'-disubstituted stilbenes and 18 samples of 3,3'-disubstituted stilbenes were synthesized, and their UV data were measured in anhydrous ethanol. Based on the UV absorption energy (wavenumber) of 3,4'-disubstituted stilbenes, the excited-state substituent constants s ex CC m ð Þ of metasubstituent were determined by means of curve-fitting. The availability of s ex CC m ð Þ was confirmed by the good correlation with the UV absorption energy of 3,4'-disubstituted stilbenes and 4,4'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 15 publications
(27 reference statements)
0
38
0
Order By: Relevance
“…At that time, there were no σcc)(mex values of meta‐substituent so that the prediction of UV–Vis absorption ν max values of the meta‐substituted benzylideneanilines couldn't be carried out. Recently, Cao et al proposed excited‐state substituent constants σcc)(mex values for several meta‐substituents, which makes it possible to calculate the UV–Vis absorption ν max values of 3,4′/4,3′‐disubstituted benzylideneanilines by using Eqn . Compared with the molecular structure of 4,4′‐disubstituted benzylideneanilines, we think, the 3,4′/4,3′‐disubstituted benzylideneanilines should have different UV–Vis absorption ν max values.…”
Section: Molecular Designmentioning
confidence: 99%
See 2 more Smart Citations
“…At that time, there were no σcc)(mex values of meta‐substituent so that the prediction of UV–Vis absorption ν max values of the meta‐substituted benzylideneanilines couldn't be carried out. Recently, Cao et al proposed excited‐state substituent constants σcc)(mex values for several meta‐substituents, which makes it possible to calculate the UV–Vis absorption ν max values of 3,4′/4,3′‐disubstituted benzylideneanilines by using Eqn . Compared with the molecular structure of 4,4′‐disubstituted benzylideneanilines, we think, the 3,4′/4,3′‐disubstituted benzylideneanilines should have different UV–Vis absorption ν max values.…”
Section: Molecular Designmentioning
confidence: 99%
“…It can be seen that the UV–Vis absorption ν max values of compounds XBAY can be calculated only known of the σ and σCCex constants . Therefore, we try to employ Eqn to design benzylideneanilines with the given UV–Vis absorption ν max values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2008, Cao et al [19] proposed an excited-state substituent constant σ ex CC to express the effect of substituents on the properties of compounds at excited state, and then we used the σ ex CC to correlate quantitatively the UV absorption spectra and reduction potential of substituted benzene, substituted stilbene, and Schiff bases. [20][21][22][23][24][25][26] We observed that the UV absorption spectra were mainly affected by the σ ex CC for the substituted benzene and substituted stilbene compounds, while the UV absorption spectra of Schiff bases were affected by both substituents σ ex CC and σ. The constant σ ex CC , proposed by Cao, [19] provides a convenience for investigating quantitatively optical properties of organic compounds, but, up to now, there are only a few number of substituents being determined the σ ex CC values, which cannot far meet the needs of investigation and application.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, if we want to increase σ ex CC values of certain groups, we have to do more experiments. [21,27,28] As we know, furyl and thienyl are common optically active groups and appear more frequently in organic compounds, and the extraction of their σ ex CC is an important work for the study of optical materials. Because there is difficult to synthesize compounds with the molecular skeleton of XArCH═CHArY (X = 2furyl, 3-furyl, 2′-methyl-2-furyl, 2-thienyl, 3-thienyl, and 2′-methyl-2-thienyl), we design and synthesize the series of target compounds (XCH═CHArY) and measure their longest wavelength maximum λ max (nm) of UV absorption spectra and try to determine the σ ex CC p ð Þ of furyl and thienyl by means of curve-fitting method.…”
Section: Introductionmentioning
confidence: 99%